Factors that impel individuals’ to share knowledge - Okyere-Kwakye, Eugene; Md Nor, Khalil; Ologbo, Andrew (2012)
To enhance one’s understanding of knowledge sharing, this study is aimed to investigate the factors that trigger individuals’ to share their knowledge.Based on the Social Exchange Theory, we proposed that trust and mutual reciprocity may influence knowledge sharing behaviour of which a research model was developed.In addition, drawing from previous studies, we added another construct i.e., perceived enjoyment to the research model.One hundred and twenty questionnaires were distributed to administrators at one public university in Malaysia. Multiple regression was employed to analyze the data. The results indicate that perceived enjoyment and trust have a significant influence on knowledge sharing.Surprisingly, the effect of mutual reciprocity was not supported.Practical implications of the findings are discussed.